2018
DOI: 10.1210/er.2018-00065
|View full text |Cite
|
Sign up to set email alerts
|

Two Hormones for One Receptor: Evolution, Biochemistry, Actions, and Pathophysiology of LH and hCG

Abstract: LH and chorionic gonadotropin (CG) are glycoproteins fundamental to sexual development and reproduction. Because they act on the same receptor (LHCGR), the general consensus has been that LH and human CG (hCG) are equivalent. However, separate evolution of LHβ and hCGβ subunits occurred in primates, resulting in two molecules sharing ~85% identity and regulating different physiological events. Pituitary, pulsatile LH production results in an ~90-minute half-life molecule targeting the gonads to regulate gameto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 142 publications
(124 citation statements)
references
References 396 publications
0
122
0
2
Order By: Relevance
“…Of note, all available results on this topic used hCG to stimulate intra-testicular testosterone production rather than the physiological hormone LH. Although LH and hCG act on the same receptor, recent studies demonstrated different signal transduction pathways at the cellular level and different clinical outcomes in vivo, at least in women undergoing assisted reproduction [2,154]. The reason for using hCG instead of LH is more related to historical and practical reasons (availability, half-life, and costs) than to scientific evidence.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, all available results on this topic used hCG to stimulate intra-testicular testosterone production rather than the physiological hormone LH. Although LH and hCG act on the same receptor, recent studies demonstrated different signal transduction pathways at the cellular level and different clinical outcomes in vivo, at least in women undergoing assisted reproduction [2,154]. The reason for using hCG instead of LH is more related to historical and practical reasons (availability, half-life, and costs) than to scientific evidence.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Therefore, there is the need to add hCG (from the urine of pregnant women) to modern hMG preparations. Considering hCG potency and half-life, no attempts were made to obtain pituitary LH from urine in the certainty that the two gonadotropins had the same biological effect [2]. Now that recombinant gonadotropins are available, the new evidence on the differences between LH and hCG action should be considered and could open further perspectives in the potential therapeutic role of LH in stimulating testicular function.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome the relatively short half-life of FSH, which requires daily administration, a new recombinant molecule with a prolonged action was produced in transfected CHO cells [81], corifollitropin alpha (Elonva ® ; MSD, Readington, NJ, USA). This chimeric molecule includes the sequence encoding the CTP extension of hCGβ fused to the human FSHβ subunit, which bears four O-linked glycosylation sites and provides extended half-life [82,83]. Corifollitropin alpha has slower absorption and longer elimination half-time than follitropin alpha [84] so that one single injection can replace seven daily injections of follitropin alpha [85][86][87].…”
Section: Fsh In Therapymentioning
confidence: 99%
“…Most studies using gonadotropins were based on hCG, instead of the physiological hormone LH, which was present in the old hMG preparations but is absent from the modern, highly purified urinary gonadotropins. In light of the different intracellular signaling pattern mediated by LH and hCG [83] in Leydig cells [104,105], and considering that hCG has no functions in the adult male, where androgen production is supported by LH action, hCG might not be the optimal therapy and this possibility should be verified in future studies. In any case, intratesticular testosterone plays a central role in sustaining spermatogenesis, and this can be induced through the steroidogenic action of hCG, while FSH contribution would be mainly supportive of sperm quality [106,107].…”
Section: Fsh Use In Hypogonadotropic Hypogonadism: State-of-the-artmentioning
confidence: 99%